The impacts of differentiated markets on the relationship between dairy processors and smallholder farmers in the Peruvian Andes. (January 2015) - Fuentes Navarro, E.; Faure, G.; Cortijo, E.; De Nys, E.; Bogue, J.; Gómez, C.; Mercado, W.; Gamboa, C.; Le Gal, P.-Y.
Highlights: Large diversity of supply channels (formal and informal ones) co-exist in the area. Milk flows between actors based on a mix of competition and complementarity process. Organization is flexible enough to respond to the demand for dairy products in Lima. Smallholder farmers are included in the dairy sector without making big investments. Informal sector has high profits per liter of milk but remain sensitive to controls. Abstract: The structure of dairy supply chains in developing countries often shows a large diversity of organization usually based on smallholder farmers' involvement. This paper investigates how a dual supply chain combining both formal and informal markets with predominantly smallholder farmers impacts farmer–processor interactions at technical and organizational level in a Peruvian Andean valley. The analysis is based on three complementary field studies conducted between 2009 and 2012. Results show a large diversity of supply channels in formal and informal chains. Milk flows are observed between formal and informal processors based on a mix of competition and complementarity depending on the season of the year and the level of consumer demand. Smallholder farmers can change processors frequently according to the milk price and services offered, since no contracts link stakeholders. This organization allows smallholder farmers to be involved in the dairy sector but with low profitability. While the informal sector shows better profits per liter of milk than the formal ones, it remains sensitive to the State's willingness to apply stricter quality regulations.